Advances in Bacteriophage Therapy against Relevant MultiDrug-Resistant Pathogens - Antonio Broncano-Lavado; Guillermo Santamaría-Corral; Jaime Esteban; Meritxell García-Quintanilla (Antibiotics, 2021)
The increase of multiresistance in bacteria and the shortage of new antibiotics in the market is becoming a major public health concern. The World Health Organization (WHO) has declared critical priority to develop new antimicrobials against three types of bacteria: carbapenem-resistant A. baumannii, carbapenem-resistant P. aeruginosa and carbapenem-resistant and ESBL-producing Enterobacteriaceae. Phage therapy is a promising alternative therapy with renewed research in Western countries. This field includes studies in vitro, in vivo, clinical trials and clinical cases of patients receiving phages as the last resource after failure of standard treatments due to multidrug resistance. Importantly, this alternative treatment has been shown to be more effective when administered in combination with antibiotics, including infections with biofilm formation. This review summarizes the most recent studies of this strategy in animal models, case reports and clinical trials to deal with infections caused by resistant A. baumannii, K. pneumoniae, E. coli, and P. aeruginosa strains, as well as discusses the main limitations of phage therapy.